2004
DOI: 10.1300/j028v15n03_11
|View full text |Cite
|
Sign up to set email alerts
|

Growth and Feed Conversion of Sub-Yearling Atlantic Sturgeon, Acipenser oxyrinchus, at Three Feeding Rates

Abstract: Growth and survival of fingerling Atlantic sturgeon, Acipenser oxyrinchus, were examined at three different feed rates. Sturgeon (mean initial weight±SD of 28±12 g) were offered a closed-formula, commercially-available sturgeon diet (48.5% protein, 16.2% fat, 9.9% moisture, 7.6% ash, 0.5% fiber and 17.4% nitrogen free extract) via 24-hour, time-controlled feeders at rates of 1.5, 3.0, and 4.5% body weight per day (BW/day). Mean water temperature was 16.8°C. After 49 days of feeding, final length, final weight … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
12
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(15 citation statements)
references
References 15 publications
3
12
0
Order By: Relevance
“…In this study, beluga sturgeon grew well throughout the experiment. This growth rate is comparable with or even higher than those reported by Jodun (2004) in Atlantic sturgeon, Vaccaro et al. (2004) in A. naccarii × A. baerii and Mohseni et al.…”
Section: Discussionsupporting
confidence: 85%
“…In this study, beluga sturgeon grew well throughout the experiment. This growth rate is comparable with or even higher than those reported by Jodun (2004) in Atlantic sturgeon, Vaccaro et al. (2004) in A. naccarii × A. baerii and Mohseni et al.…”
Section: Discussionsupporting
confidence: 85%
“…Feeding frequency should target optimal feed intake and the growth (Mohseni et al, 2006). Several studies have reported the effects of feeding rate on the growth performance of white sturgeon (Deng et al, 2003;Hung et al, 1995), Atlantic sturgeon (Acipenser oxyrinchus) (Jodun, 2004;Kelly and Arnold, 1999), shortnose sturgeon (Acipenser brevirostrum) (Giberson and Litvak, 2003), Persian sturgeon (Acipenser persicus) (Yousefpour et al, 1998), and great sturgeon (Mohseni et al, 2006;Pourali et al, Aquaculture 448 (2015) …”
Section: Introductionmentioning
confidence: 99%
“…A few studies have considered the influence of the feeding rate on sturgeon (Hung et al., 1995; Yousefpour et al., 1998; Kelly and Arnold, 1999; Hung and Deng, 2002; Deng et al., 2003, 2005; Giberson and Litvak, 2003; Rad et al, 2003; Jodun, 2004; Mohseni et al., 2006).…”
Section: Introductionmentioning
confidence: 99%